A question of belief! Study of kindergarten teachers' beliefs about physical activity and sport - Kathrin Freudenberger (Bern Open Publishing, 2023)
Introduction Movement is the motor of young children's overall development and must be recognized in all its facets and enabled and encouraged in various contexts. Kindergarten - as the first compulsory educational institution in Switzerland - has a special responsibility in regards to this. Kindergarten teachers play a key role in educational processes. The quality of teaching is influenced by their professional competency. Beliefs form an important part of this competency and they have an action-guiding effect (Baumert & Kunter, 2013). The individual ideologies and beliefs of teachers impact their lesson content and design, as well as their perception of children's physical movement during the lesson. Despite this, studies of teachers' beliefs about physical activity and physical education in kindergarten are scarce. Results are not available on learning content, process, perception of children's physical activity behavior and contextual conditions in the Swiss-German educational environment are not available. Methods This study uses an exploratory research design, compiling the beliefs of seven Swiss Kindergarten teachers through guided interviews. Those beliefs were evaluated using the Documentary Method following Nohl (2017; Freudenberger, 2022). Results The results indicate that teachers use the Swiss curriculum ("Lehrplan 21") as a rough guide. Their interests drive lesson implementation, along with children's approach to self-organized play. Teachers put together a gymnastics lesson in terms of the competence area "movement on equipment" in the gymnasium itself. In the kindergarten rooms, they also use movement to structure the class, set the rhythm, and reward students. Nevertheless, the teachers express the desire for support in designing the indoor and outdoor spaces in a way that stimulates movement. However, teachers perceive a decline in children's motor skills. Discussion/Conclusion The results of the interview study make it possible to describe the convictions of kindergarten teachers. They can be used for the quality development of teaching in physical activity and sport in kindergarten and form an orientation framework for the content conception of training and further education of teachers. The study identifies the following key topics to guide the conceptual design of these qualifications: To make full use of the educational and developmental potential of physical activity and sports already in kindergarten, the relevance of physical activity, play and sports must be precisely explained and conveyed in qualification courses. Teachers should be trained in using assessments for physical behavior of the students more objectively and then to support them in a targeted manner. Furthermore, all competency areas of the Swiss Curriculum should be taught - by using various teaching materials by means of diverse teaching methods. More targeted support in designing indoor and outdoor spaces to stimulate movement in kindergarten could firstly counteract the increasing restriction of children's play spaces in the home environment (Zimmer, 2020) and secondly awaken children's curiosity about the world, expand their repertoire of actions and encourage them in the perception of their autonomy potential (Egger, 2019, p. 291f). References Baumert, J., & Kunter, M. (2013). Professionelle Kompetenz von Lehrkräften [Professional competence of teachers]. In I. Gogolin, H. Kuper, H.-H. Krüger & J. Baumert (Hrsg.), Stichwort: Zeitschrift für Erziehungswissenschaft (S. 277-337). Springer VS. Egger, J. (2019). Häuser machen Schule. Eine architektursoziologische Analyse gebauter Bildung [Houses make school. An architectural-sociological analysis of built education]. Springer VS. Freudenberger, K. (2022). Eine Frage der Haltung. Überzeugungen von Lehrpersonen zum Bewegung- und Sportunterricht im Kindergarten [A question of attitude. Teachers' beliefs about physical activity and sport teaching in kindergarten]. [Unpublished master's thesis]. Universität Basel. Nohl, A.-M. (2017). Interview und Dokumentarische Methode: Anleitungen für die Forschungspraxis [Interview and documentary method: Guidance for research practice]. Springer. Zimmer, R. (2020). Handbuch Bewegungserziehung: Grundlagen für Ausbildung und pädagogische Praxis [Handbook on physical education: Basics for training and pedagogical practice]. Herder.